Epidemiology of neurodegenerative diseases in the East African region: A meta-analysis - Onohuean, Hope; Akiyode, Abraham Olutumininu; Akiyode, Oluwole; Igbinoba, Sharon Iyobor; Alagbonsi, Abdullateef Isiaka (Frontiers in Neurology, 2022)
Abstract Introduction: There is a scarcity of epidemiological data on neurodegenerative diseases (NDs) in East African. This meta-analysis sought to synthesized scientific evidence on NDs in the region. Method: Articles were retrieved from electronic databases following PRISMA standard. Results: Forty-two studies reviewed and 25 were meta-analyzed with a random-effects model. The pool estimate proportion of 15.27%, 95%CI (0.09–0.23), (I2=98.25%), (Q=1369.15, p<0.0001) among a population of 15,813 male/female and 1257 with ND. Epidemiological characteristics associated with ND includes Dyskinesias prevalence 55.4%, 95% CI (13.5; 90.9), I2 (96%) and subsistence farming prevalence 11.3%, 95% CI (5.8; 20.9), I2 (99%). Publication bias by Egger test shown (z=4.1913, p<0.0001), rank correlation test using Kendall's model indicates (tau=0.1237, p=0.3873). Heterogeneity (R2 design=5.23%, P design <0.0001; R2 size=52.163%, P size <0.001; and R2 period =48.13, P period <0.0001. Covariates (R2 design+size+period=48.41%, P< 0.001). Conclusion: There is a regional rise of NDs in East African region.